Understanding The Effects Of Ewom On Direct Sales Through The Information Adoption Model - Chan, Joon Yang; Low, Boon Xian; Low, Joh Ann; Loo, Wen Lin; Tan, Kin Yu (2017)
In the direct sales industry, leveraging social networking sites has dramatically boost the industry to new heights. The need to understand the effects and influencing factors of eWOM messages on youth’s engagement in direct selling can provide an insight to the direct sales industry as well as to both business and government sector. Based on the Information Adoption Model, the present study proposed a conceptual framework to understand how eWOM communication influences youth in inducing purchase decision and intention to partake in MLM. Findings revealed that argument quality (M = 4.279, SD = .384), source credibility (M = 4.241, SD = .487) and tie strength (M = 4.035, SD = .486) positively impacts information adoption (M = 4.316, SD = .450) through information usefulness (M = 4.250, SD = .433) in the direct sales industry. Argument quality is found to have the strongest influence to information adoption among youths (r = 0.481, p < 0.001). The researchers concluded that the quality of the information (argument) perceived by the consumers will strongly influence whether the information will be perceived as useful and will lead to information adoption. The results signifies that the impact of central cues (argument quality) increases, the impact of peripheral cues (source credibility and tie strength) will inevitably decrease as stated and supported by O’Keefe and Jackson (1995). The researchers also affirmed that information usefulness and information adoption has a strong relationship (r = 0.529, p <0.05) which signifies that when the higher the information is proven to be useful, the higher probability the information will be adopted. In the context of this study, it would illustrate that when youth perceived that the direct sales product or service is useful, the higher probability that they will buy and recommend it in their social groups.